"Structure and Model Approach" Versus "Imaginative Learning": Reflections on a Complementary Theory - Rhode-Jüchtern, Tilman (Journal of Geography Education, 2005)
The text deals with the question of how school enables young pupils to recognize structures of the outer world. Helmuth Köck answers the question refering to physiological and psychological presuppositions of learning according to Spitzer. The author of this abstract counters Köcks statements point by point:1. Geographical knowledge of the world is rule abiding. Yet, in order to get an insight into the making of these rules, one has to read stories / tales (narrative geography) and to interprete them personally. If this attempt fails -as it happens quite often- pupils are demotivated. Correlation and interrelation cannot be taught. It needs to be realized by the individual. And this is a subjective learning process.2. Geography cannot be reduced to facts and structures. Values and aims are also of great importance. Very often knowledge contradicts acting and vice versa. Thus, despite of only teaching common knowledge of structures, worthwhile every day problems have always to be at the centre of discussion.3. The brain does not reflect the world in the way a mirror does. However, it is the brain itself that constitutes different structures. In most cases systems do have more than two variable items. Therefore, they aren't simply causal nor predictable, but they are chaotic.4. Teachers are not only supposed to teach contents, but also do they have to focus on educational processes. As a consequence, learning is based on more than just on categories, it is rather based on the personal development of each pupil. In this respect meaningful settings, new input and pupils' curiosities are inevitable constituents of a learning process. Teachers do not need to know all structures. They dare to doubt and to have a personal attitude towards the topics.Imaginative and comprehension intensive learning is an alternative educational approach to the question. Learning processes are organised in four steps: to tie on experiences, to build up imaginations, to grasp and to form terms and concepts, to reflect. Geography is not meant to standardize a world view, but to open it up in or to expose and to see it's plurality and to reflect upon it.